Revisiting the gene loss of respiratory requirements for Salmonella Typhimurium and Salmonella Enteritidis in the chicken infection model - Monte, Daniel F. M. [UNESP]; Saraiva, Mauro de Mesquita Souza [UNESP]; Cabrera, Julia Memrava [UNESP]; Almeida, Adriana Maria de [UNESP]; Paiva, Jacqueline Boldrin de; Muniz, Lauanda Monteriro; Lima, Tulio Spina de [UNESP]; Freitas Neto, Oliveiro Caetano de; Barrow, Paul A.; Berchieri Junior, Angelo [UNESP] (Springer Nature, 2025)
Salmonella strains are able to use tetrathionate as a terminal respiratory electron acceptor. Here we report the role of ttrRSBCA operon in Salmonella-challenged broilers. Signature-tagged mutagenesis was used to construct defective strains of S. Typhimurium and S. Enteritidis carrying deletions in the whole ttr operon (ΔttrRSBCA) followed by measurement of faecal shedding and cecal colonization counts. Regarding fecal excretion, S. Typhimurium mutant strain harbouring deletion in ttrRSBCA were excreted in similar numbers than the parental wild-type strain during the experimental period, while the SEΔttrRSBCA strain was excreted slightly less in comparison to the wild-type strain. Furthermore, our findings revealed partial attenuation of STMΔttrRSBCA at 2, 5, 7, and 28 days post-infection (dpi), whereas the SEΔttrRSBCA strain was recovered in lower numbers compared to the parental strain at 5, 14, and 28 dpi. These results indicate that such mutations must be accompanied by other genetic changes to obtain a complete attenuation.